IN VITRO TOXICITY OF CYPERMETHRIN AND DELTAMETHRIN ON THE CATTLE TICK Rhipicephalus microplus - CHARLIE-SILVA, I.; SOUZA, L. M.; BELO, M. A. A.; MORAES, A. C.; PRADO, E. J. R.; MOLENTO, M. B.; MARCHIORI-FILHO, M. (Ars Veterinaria, 2018)
The objective of this work was to evaluate the efficacy of cypermethrin 15% and deltamethrin 25% of the cattle tick Rhipicephalus microplus, using immersion test of engorged females (ITEF) and impregnated Pasteur pipette (PIPT). The following dilutions were used: T1 =1/1000 mL (v/v), T2 = 2/1000 mL, T3 = 4/1000 mL and T4 = 8/1000 mL, respecting the dosages prescribed by the manufacturers for both pyrethroids. The Experiment I used adult females, and the acaricidal efficacy was tested on engorged females, that were collected separately from ten dairy herds in the Descalvado region, SP. The data revealed that the efficacy for cypermethrin ranged from 0.0 to 95.9% and for deltamethrin was 34.4% to 99.2%. We have observed that the efficacy of deltamethrin and cypermethrin was higher than 95%, in only four farms. Treatment with cypermethrin at 8/1000 mL dilution resulted in 100% of efficacy against larvae after 120 minutes. Deltamethrin at 8/1000 mL dilution resulted in 100% of larvae exhibiting paralysis after 60 minutes. The data revealed that the efficacy for cypermethrin ranged from 0.0% to 95.9% and for deltamethrin was 34.4% to 99.2%. We have observed that the efficacy of deltamethrin and cypermethrin was higher than 95%, in only four farms. The experiment II used the PIPT against larvae and the efficacy of the same products was checked at 5, 10, 20, 30, 60, 120, 360 and 720 min post-treatment. Treatment with cypermethrin at 8/1000 mL dilution, resulted in 100% efficacy against larvae after 60 min and 100% of larvae treated with deltamethrin presented paralysis 30 min post-treatment with the dilution of 8/1000 mL. Although both pyrethroids were 100% efficacious against larvae, the low percentage of adulticidal efficacy confirms the existence of resistant strains of this tick species. However, in four herds cypermethrin and deltamethrin were effective in controlling R. microplus, reinforcing the importance of performing immersion test of engorged females before prescribing treatments to dairy cattle, not only in this region but to the entire country.